TEACHING VOCABULARY BY USING PICTURES TO THE SECOND YEAR STUDENTS OF SMP NEGERI 1 EMBALOH HILIR KAPUAS HULU IN ACADEMIC YEAR 2007/2008 - Desi Sri Astuti (Jurnal Pendidikan Bahasa, 2014)
AbstractThe purpose of this research is to “Investigate whether or not the use of   pictures improves the students’ mastery of vocabulary of the second year students of SMPN 1 Embaloh Hilir Kapuas Hulu in academic year 2007/2008. The methodology of this research is pre-experimental study design. It is employed and designed with measurement of the students “pre-test and post-test total scores”, the students mean score of each test (pre-test and pos-test), and the test of significance. Based on the computation of t-value, the Alternative Hypothesis is accepted and the Null Hypothesis is rejected. Teaching vocabulary by using pictures to the  second year students of SMPN 1 Embaloh Hilir Kapuas Hulu in academic year 2007/2008 is able to improve the students’ mastery of vocabulary. Keyword : pictures, vocabulary